1994
DOI: 10.1016/1010-7940(94)90091-4
|View full text |Cite
|
Sign up to set email alerts
|

Early and late results following combined coronary bypass surgery and mitral valve replacement

Abstract: To study the effect of various perioperative and operative variables, we analysed the results of 66 consecutive patients undergoing mitral valve replacement (MVR) and coronary artery bypass grafting (CABG). The mean age was 61.2 years (34 males and 32 females), the mean follow-up 54.71 +/- 7.8 months. The hospital mortality rate was 7.6% (5/66). New York Heart Association (NYHA) functional class (P < 0.01), left ventricular global wall motion score (increased scores indicating impaired function, P = 0.005) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 5 publications
0
14
0
Order By: Relevance
“…Five-and 10-year survival of 61% and 38% in this group are rates comparable with those of other reports of primary MVR and CABG. 1,18,22 EFϽ50%, NYHA class IV, use of the intra-aortic balloon pump, and urgent or emergency operation were significant predictors of late death. Left ventricular dysfunction has been found to be a significant predictor of adverse long-term survival in many studies of MVR or MVR and CABG.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Five-and 10-year survival of 61% and 38% in this group are rates comparable with those of other reports of primary MVR and CABG. 1,18,22 EFϽ50%, NYHA class IV, use of the intra-aortic balloon pump, and urgent or emergency operation were significant predictors of late death. Left ventricular dysfunction has been found to be a significant predictor of adverse long-term survival in many studies of MVR or MVR and CABG.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies of primary MVR and MV repair with CABG have not shown a consistent correlation between origin and early mortality. 1,9,22,23 On the other hand, others have found that ischemic mitral regurgitation was a predictor for early death after combined MVR and MV repair and CABG. 14,24 Our failure to find this may reflect the small numbers in each group in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Most modern series quote a variable, but greater early mortality rate of 6.3 to 13.5% compared with 1.7 to 5.5% for isolated CABG or AVR procedures. [4][5][6][7][8] Many risk factors have been identified for an increased mortality including age, diabetes mellitus, renal dysfunction, New York Heart Association (NYHA) class, poor left ventricular function, ischemic valve dysfunction, urgent operation, increased cross-clamp time and bypass time, blood transfusion, and prior cardiac surgery. 4,6,[8][9][10][11][12][13] Despite cigarette smoking being a powerful risk factor for coronary artery disease, myocardial infarction, and cardiac death, its effect on outcomes after combined CABG and AVR remains equivocal.…”
Section: Introductionmentioning
confidence: 99%
“…Prolonged CPB and ACC times have been known contributory factors to elevated operative risk in concomitant CABG /MVR procedures 19,20 .…”
Section: Resultsmentioning
confidence: 99%